Applying SAXS to study the structuring of Fe3O4 magnetic nanoparticles in colloidal suspensions - Jenny Mera Cordoba; Diego Fernando Coral-Coral (Dyna, 2019)
In this work, Small Angle X-ray Scattering (SAXS) patterns, obtained from two different aqueous colloidal suspensions of magnetite nanoparticles electrostatically stabilized with citric acid, were fitted using three different mathematical models in order to describe the particle size distribution and aggregation state. The colloidal suspensions differ in the mean particle size (4.5±1.0 nm and 5.5±1.1 nm) and the aqueous stabilization, allowing control of the strength of the interaction strength between particles. The models used for SAXS analysis, reveal that the particles are almost spherical with a broad size distribution, and that particles in each suspension are aggregated and are subject to an attractive interaction potential, typical for magnetic nanoparticles. For the better-stabilized sample, ramified chain-like aggregates were found, and for the less-stabilized sample, a more compact structure was determined. The size distribution obtained by applying SAXS mathematical models are in agreement with the size distribution determined using Transmission Electronic Microscopy (TEM)